2010
DOI: 10.1213/ane.0b013e3181ee7bba
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Transversus Abdominis Plane Block Provides Effective Analgesia After Appendectomy in Children

Abstract: Unilateral TAP block, as a component of a multimodal analgesic regimen, provided superior analgesia compared with placebo in the first 48 postoperative hours after appendectomy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 16 publications
4
119
1
5
Order By: Relevance
“…6). Compared with the control group, the TAP block reduced the 24-hr pain score 20,30,31,39,48,62 by 1.7 (95% CI, App/IS = appendectomy /inguinal surgery; CD = Cesarean delivery; CI = confidence interval; I 2 = heterogeneity; IAW = inside abdominal wall; TAP = transversus abdominal plane block; US = ultrasound -2.4 to -1.0; P \ 0.001) and 24-hr morphine consumption 30,39,62 by 20.4 mg (95% CI, -29.7 to -11.1; P \ 0.001) ( Table 2).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 83%
See 2 more Smart Citations
“…6). Compared with the control group, the TAP block reduced the 24-hr pain score 20,30,31,39,48,62 by 1.7 (95% CI, App/IS = appendectomy /inguinal surgery; CD = Cesarean delivery; CI = confidence interval; I 2 = heterogeneity; IAW = inside abdominal wall; TAP = transversus abdominal plane block; US = ultrasound -2.4 to -1.0; P \ 0.001) and 24-hr morphine consumption 30,39,62 by 20.4 mg (95% CI, -29.7 to -11.1; P \ 0.001) ( Table 2).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 83%
“…In inguinal hernia surgery and appendectomy, compared with the control group, the overall analysis showed that the TAP block reduced the six-hour pain score 20,30,31,39 by 2.5 (95% CI, -4.7 to -1.2; P = 0.001) and the 12-hr pain score 20,30,31,39,48 by 3.9 (95% CI, -5.0 to -2.9; P\0.001) (Fig. 6).…”
Section: Transversus Abdominal Plane Block In Appendectomy and Inguinmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 1 showed the flow diagram for the study identification and selection process. After reading and evaluating the titles, abstracts and full texts, 5 studies with 257 children ultimately met our inclusion criteria (21)(22)(23)(24)(25). The characteristics and outcomes of each included studies were summarized in table.…”
Section: Search Resultsmentioning
confidence: 99%
“…However, a number of studies showed a comparable efficacy of the blindly performed TAP block to ultrasound guided ones after abdominal surgery for variety of surgical cases if done appropriately [7,13]. Factors determining the efficacy of the block can either be the result of technical trouble in performing, surgical and patient factors [14,15].…”
Section: Introductionmentioning
confidence: 99%